2010
DOI: 10.1002/syn.20818
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular events of dopamine D1 receptor‐mediated tau phosphorylation in SK‐N‐MC cells

Abstract: Microtubules are involved in the formation of axons and dendrites, maintenance of neuronal morphology, and cellular trafficking. Recent studies suggest that drugs affecting dopamine activity in the brain can induce cytoskeletal modifications. For instance, we have demonstrated in acute rat brain slices a molecular chain of events connecting dopamine D1 receptor to aberrant phosphorylation of the microtubule-associated protein tau. However, the molecular and cellular effects of tau phosphorylated by means of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Other neurotransmitter receptor systems have so far not been implicated in the regulation of Tau phosphorylation with the exception of dopamine. In SK-N-MC cells and striatal neurons, Tau was phosphorylated at Ser-199/Ser-202 in response to dopamine D1 receptor activation in a Ca 2ϩ -and PKA-dependent manner (41,42). Interestingly, we found that GABA A receptor activators, as well as a dopamine D1/D2 receptor antagonist, increased Pin1-Tau interaction and Tau phosphorylation at Ser-199/Ser-202/Thr-205 (in case of GABA A activation; the dopamine D1/D2 antagonist was not analyzed further in this study).…”
Section: Discussionmentioning
confidence: 99%
“…Other neurotransmitter receptor systems have so far not been implicated in the regulation of Tau phosphorylation with the exception of dopamine. In SK-N-MC cells and striatal neurons, Tau was phosphorylated at Ser-199/Ser-202 in response to dopamine D1 receptor activation in a Ca 2ϩ -and PKA-dependent manner (41,42). Interestingly, we found that GABA A receptor activators, as well as a dopamine D1/D2 receptor antagonist, increased Pin1-Tau interaction and Tau phosphorylation at Ser-199/Ser-202/Thr-205 (in case of GABA A activation; the dopamine D1/D2 antagonist was not analyzed further in this study).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the variants in the gene encoding CK1 that phosphorylate DARPP-32 are associated with the subjective response to amphetamine in normal volunteers (Veenstra-VanderWeele et al, 2006). The other kinases that are related to the DARPP-32 signaling network, CDK5 and ERK, have been shown to contribute to the abnormal plasticity that leads to drug abuse and L-DOPA-induced dyskinesia (Aubert et al, 2005;Girault et al, 2007;Santini et al, 2007;Lebel and Cyr, 2011); however, further observations in clinical settings are necessary to support these hypotheses.…”
Section: B Abnormalities In G Protein-related Dopamine Signaling In mentioning
confidence: 99%
“…In addition to its affinity for 5‐HT7R, amisulpride also targets dopaminergic receptors that, in turn, may influence tau aggregation 31–33 . To exclude the involvement of dopaminergic signaling, we analyzed the effects of dopamine D2/D3 antagonist tiapride.…”
Section: Discussionmentioning
confidence: 99%